2014
DOI: 10.1007/s12034-014-0726-6
|View full text |Cite
|
Sign up to set email alerts
|

ALD TiO2 thin film as dielectric for Al/p-Si Schottky diode

Abstract: Electrical analysis of Al/p-Si Schottky diode with titanium dioxide (TiO 2) thin film was performed at room temperature. The forward and reverse bias current-voltage (I-V) characteristics of diode were studied. Using thermionic emission (TE) theory, the main electrical parameters of the Al/TiO 2 /p-Si Schottky diode such as ideality factor (n), zero bias barrier height (φ Bo) and series resistance (R s) were estimated from forward bias I-V plots. At the same time, values of n, φ Bo and R s were obtained from C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…For this purpose, the wafer was cleaned with trichloroethylene, acetone and methanol. Then, the surface of Si were etched in H 2 SO 4 +H 2 O 2 +H 2 O (5:1:1), 20% HF, HNO 3 + HF + H 2 O (6:1:35) and 20% HF, consecutively [20]. After each step, the wafer was rinsed by deionized water with high resistivity.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, the wafer was cleaned with trichloroethylene, acetone and methanol. Then, the surface of Si were etched in H 2 SO 4 +H 2 O 2 +H 2 O (5:1:1), 20% HF, HNO 3 + HF + H 2 O (6:1:35) and 20% HF, consecutively [20]. After each step, the wafer was rinsed by deionized water with high resistivity.…”
Section: Methodsmentioning
confidence: 99%
“…Before deposition steps, ultrasonic and chemical substrate cleaning procedures by organic solvents of CHClCCl 2 , CH 3 COCH 3 and CH 3 OH were applied for 10 min. Following to the cleaning, the surfaces of the SiC substrates were etched in a sequence of H 2 SO 4 , H 2 O 2 −HF (20%), HF (20%), a solution of 6HNO 3 :1HF:35H 2 O and finally rinsed in 18 M .cm deionized water [26][27][28][29]. Then, under 10 −7 mbar vacuum condition, highly pure (99.999%) Au metal source was thermally evaporated to form ohmic back contacts for the substrates [30].…”
Section: Methodsmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) became a promising material in different applications for its excellent optical and electrical properties and chemical stability such as large band gap, high refractive index, high dielectric constant, and highly active surface [ 1 4 ]. Traditionally, TiO 2 pigment has almost been applied to every kind of paint due to its high refractive index [ 5 , 6 ] and used as photocatalyst in the process of sterilizing, deodorizing, antifouling, and so on, which can convert light energy into electrical energy and chemical energy [ 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, metalenses at visible wavelengths with efficiencies as high as 86% have been demonstrated recently by using TiO 2 materials, in which TiO 2 could overcome the challenge of the high intrinsic losses in the visible range and realize the highly efficient metasurfaces in this region [ 12 ]. TiO 2 has been one of the most studied materials in the last decades, and numerous research concerning TiO 2 bulks and films have been already reported [ 1 4 ]. However, the research on the optical properties of TiO 2 ultrathin films, especially below 20 nm, is still rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation